2017
DOI: 10.17547/kjsr.2017.25.2.145
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of the Possibility of Loving-Kindness and Compassion Meditation for Pregnant Women: A Preliminary Study

Abstract: Loving-kindness and compassion meditation (LKCM) is known to be effective in improving mental health and interpersonal relationships. An exploratory pilot study was conducted with the aim of examining the feasibility of LKCM which known to be effective in improving mental health and interpersonal relationships for pregnant women. Measures of stress, depression, maternal fetal attachment, mindfulness and self-compassion of subjects (n=8) were obtained at baseline, and after a 4-weeks LKCM program to identify ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…For this reason, before developing a full-fledged LKCM program for MFA, a preliminary program for pregnant women was constructed and conducted by referring to the existing research and the LKCM program for the general population. As a result, LKCM confirmed the possibility that the positive emotion of the pregnant women would be improved, the mother-fetal relation could be improved positively, and the unexpected change in the fetal movement experience was confirmed (Kim MJ et al, 2017). And through structural equation modeling in Heo JM et al(2017), it was confirmed that mindfulness and positive emotion are important leading factors in MFA formation, and one of the key mechanisms is positive fetal movement experience.…”
Section: Introductionmentioning
confidence: 72%
See 4 more Smart Citations
“…For this reason, before developing a full-fledged LKCM program for MFA, a preliminary program for pregnant women was constructed and conducted by referring to the existing research and the LKCM program for the general population. As a result, LKCM confirmed the possibility that the positive emotion of the pregnant women would be improved, the mother-fetal relation could be improved positively, and the unexpected change in the fetal movement experience was confirmed (Kim MJ et al, 2017). And through structural equation modeling in Heo JM et al(2017), it was confirmed that mindfulness and positive emotion are important leading factors in MFA formation, and one of the key mechanisms is positive fetal movement experience.…”
Section: Introductionmentioning
confidence: 72%
“…The composition and contents of this session were revised and completed according to the studies conducted by Kim MJ et al(2017) and Heo JM et al(2017), existing research, and experts' feedback and consultation. The three people who provided feedback and consulting were experts on LKCM.…”
Section: Goals Of the Lkcm Program And Session Contentmentioning
confidence: 99%
See 3 more Smart Citations